BRE Promotes Esophageal Squamous Cell Carcinoma Growth by Activating AKT Signaling - Jin, Fujun; Zhu, Yexuan; Chen, Jingyi; Wang, Rongze; Wang, Yiliang; Wu, Yanting; Zhou, Pengjun; Song, Xiaowei; Ren, Zhe; Dong, Jun (Frontiers in Oncology, 2020)
Brain and reproductive organ-expressed protein (BRE) is aberrantly expressed in multiple cancers; however, its expression pattern in human esophageal squamous cell carcinoma (ESCC) and its role in ESCC progression remain unclear. In this study, we aimed to investigate the expression pattern of BRE in human ESCC and its role in ESCC progression. BRE was overexpressed in ESCC tissues compared with that in the adjacent non-tumor tissues. Forced expression of BRE was sufficient to enhance ESCC cell growth by promoting cell cycle progression and anti-apoptosis. Silencing of BRE suppressed these malignant phenotypes of ESCC cells. Mechanistic evaluation revealed that BRE overexpression activated the phosphorylation of AKT, and inhibition of the AKT pathway by MK2206 decreased the BRE-induced cell growth and apoptotic resistance in ESCC cells, highlighting the critical role of AKT signaling in mediating the effects of BRE. Moreover, the effects of BRE on ESCC cell growth and AKT activation were verified in a xenograft model in vivo. The present results show that BRE is overexpressed in ESCC tissues and contributes to the growth of ESCC cells by activating AKT signaling both in vitro and in vivo and provide insight into the role of BRE in AKT signaling and ESCC pathogenesis.